GPS Laboral: La facultad de Fiscalización del Empleador a partir de las Nuevas Tecnologías de la Información - Toyama Miyagusuku, Jorge (2014)
The authors analyze the exercise of the power of controlregarding new technologies of information. Particularly, the use of GPs Tracking as a tool that the employer relies on to verify that workers fulfill their work. Firstly, the authors explain how these technologies are used at workplaces and their lack of regulation in Peruvian Law. Then, they explain the conditions necessary for not violating the workers’fundamental rights when using this tool. Finally, they discuss the case law and precedents, as well as cases seen by theNational Labour Authority.